Evaluation of cases with pregnancy complicated by thyroid diseases - MADAZLI, Rıza; BULUT, Berk; ONCÜL, Mahmut; ARTAR, Gökhan; BENİAN, Ali (Cerrahpaşa Medical Journal, 2019)
To evaluate the outcomes of the pregnancies complicated by thyroid diseases treated at our clinic and to review the current literature. A total of 117 pregnancies complicated by thyroid diseases treated in our clinic were investigated retrospectively. Free T4 and TSH levels were assessed as thyroid function tests. While thyroid peroxidase and anti-thyroglobulin antibody levels were studied for Hashimoto’s thyroiditis, thyroid stimulating antibodies were evaluated for Graves’ disease. Cases with hypothyroidism were managed by thyroid hormone replacement therapy whereas propylthiouracyl was the drug of choice in patients who suffered hyperthroidism. Out of the 117 pregnant women with thyroid diseases included in the study, 85 had hypothyroidism and 32 had hyperthyroidism. The etiology of hypothyroidism was found to be Hashimoto’s thyroiditis in 24.7 %, iodine deficiency in 30.6 % and thyroidectomy in 44.7 %. In cases with hypothyroidism the rates of intrauterine growth retardation, preterm delivery, preeclampsia and gestational diabetes mellitus were 4.7, 7.1, 3.5 and 9.4 % respectively. In 40 % of the pregnant women with hypothyroidism, the dose of the thyroid replacment therapy has increased and no problems were recorded in the newborns. Among the cases with hyperthyroidism and pregnancy, 78.1 % had Graves’ disease and 21.9 % had hyperactive thyroid nodules. In hyperthyroidism patients, the rates of intrauterine growth retardation, preterm labor, preeclampsia and gestational diabetes were 6.2, 12.5, 9.3 and 6.3 % respectively. The fetuses and the newborns had no significant problems. The undesired consequences of the thryoid diseases for both the fetus and the mother can be prevented by the cooperative intervention of the experienced obstetricians and endocrinologists.